Global entrepreneurship past, present & future - Devinney, Timothy M. 1956- (Emerald, 2016)
The role that small- and medium-sized enterprises play in the economic development and growth of cities, regions and nations has been an increasing subject of debate and study for the last half century. This volume focuses on the opportunities and challenges that entrepreneurs and small- and medium-sized enterprises (SMEs) face in a world of global competition. The papers therein provide an overview of successful strategies that global entrepreneurs and SMEs have employed that have allowed them to establish regional and international footprint and of how local resources, culture and managerial capabilities have contributed to startups global success. In doing so it highlights original, edgy ideas and theoretical advances that will provide the foundation for future doctoral dissertations and other research projects on international entrepreneurship.
Keywords: International business enterprises.; Entrepreneurship.; elektronické knihy; electronic books